2019
DOI: 10.1021/acs.jmedchem.8b02026
|View full text |Cite
|
Sign up to set email alerts
|

Development of Covalent Ligands for G Protein-Coupled Receptors: A Case for the Human Adenosine A3 Receptor

Abstract: The development of covalent ligands for G protein-coupled receptors (GPCRs) is not a trivial process. Here, we report a streamlined workflow thereto from synthesis to validation, exemplified by the discovery of a covalent antagonist for the human adenosine A3 receptor (hA3AR). Based on the 1H,3H-pyrido[2,1-f]purine-2,4-dione scaffold, a series of ligands bearing a fluorosulfonyl warhead and a varying linker was synthesized. This series was subjected to an affinity screen, revealing compound 17b as the most pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…Determination of washout resistance by radioligand binding is a frequently used method for the validation of a postulated irreversible interaction between a potential covalent ligand and the targeted receptor [15][16][17][18][19][20][21][22][23]. In this experimental design, the bound ligand 44 was washed out after the preincubation with hH 3 R expressing cell homogenate and showed a concentration-dependent labeling of the receptor, while the non-covalent control 42 and reference ligands recovered radioligand binding to vehicle levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of washout resistance by radioligand binding is a frequently used method for the validation of a postulated irreversible interaction between a potential covalent ligand and the targeted receptor [15][16][17][18][19][20][21][22][23]. In this experimental design, the bound ligand 44 was washed out after the preincubation with hH 3 R expressing cell homogenate and showed a concentration-dependent labeling of the receptor, while the non-covalent control 42 and reference ligands recovered radioligand binding to vehicle levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of kinases the use of TCIs has resulted in marketed drugs in past years [12], while the progress in covalent GPCR ligands is still limited in comparison [13]. Nonetheless, aided by advances in GPCR crystallography, covalent ligands targeting the orthosteric binding site of GPCRs have been disclosed [14][15][16][17][18][19][20][21][22][23]. The targeted GPCR residue is mostly a cysteine with diverse warheads being used, such as a disulfide [17,19,23], isothiocyanate [18], or Michael acceptor [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in the non-xanthine family, several examples of irreversible AR antagonists have been reported [56][57][58][59].…”
Section: Covalent Ligandsmentioning
confidence: 99%
“…A quite similar approach has been utilized for developing covalent human A 3 AR antagonists, leading to a derivative named LUF7602 (4-((3(8-methoxy-2,4-dioxo-3-propyl-3,4-dihydropyrido [2,1-f ]purin-1(2H)yl)propyl)carbamoyl)benzenesulfonyl fluoride, 25) [57] and a pyrazolo-triazolopyrimidine compound (26) [59]. The first one showed that tyrosine 265 was involved in the covalent binding, while compound 26, through the help of computational studies, suggested that serine 247 or cysteine 251, both in TM6, could be responsible for covalent binding.…”
Section: Covalent Ligandsmentioning
confidence: 99%